Any Portal in a Storm? Collaborative and crowdsourced maps in response to Typhoon Yolanda/Haiyan, Philippines - Turk, Catherine (Journal of Contingencies and Crisis Management, 2020)
The promises of crowdsourcing volunteered geographic information (VGI) for providing timely information about crises were recognized at least a decade ago. While cartographers and developers hone the accuracy of maps and data, social scientists critique these technologies through various theoretical lenses: in terms of knowledge politics of digital humanitarianism; as tools of neoliberal governance; and as examples of datification supporting automated or remote government. Amidst all these claims, it is time to return to the maps themselves, as empirical examples, considering the information they actually provide. This paper examines crowdsourced and collaborative maps from late 2013 following Typhoon Yolanda/Haiyan in the Philippines. Various humanitarian, mapping, and media organizations produced maps in response to the typhoon. Close qualitative analysis of map content queries what these maps reveal about the disaster and whether the maps really produce the information that proponents claim. Analysis of data curated in each map reveals that much of the situational information being mapped is already available elsewhere and that few new ground truths have emerged through these projects. By demonstrating the limitations of the information mediated in these maps, the findings have practical and policy implications for disaster practitioners and digital volunteers intending to help disaster response.
CRIS-Team Scopus Importer:2020-11-06
Keywords: critical cartography; crowdsourcing; digital humanitarians; disaster response; volunteered geographic information